Efficacy of tocilizumab treatment in cerulein-induced experimental acute pancreatitis model in rats - Hançerli, Yusuf; Kaplan, Mustafa; Tanoğlu, Alpaslan; Yeşilbaş, Soner; Küçükodacı, Zafer; Yıldırım, Muhammet; Narlı, Gizem; Sakin, Yusuf Serdar (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Acute pancreatitis (AP) is a disease that can cause local and systemic complications that may have high morbidity and mortality. Currently, there is not any specific treatment for AP. In this study, we created an experimental model of AP in rats, and we aimed to demonstrate the histological effectiveness of tocilizumab treatment that antagonizes interleukin-6 (IL-6), one of the key cytokines in the development of AP. Materials and Methods: Forty-eight rats were divided into six groups for this study. AP model was created by subcutaneous injections of cerulein (20 μg/kg) four times at 1-h intervals. Tocilizumab 4 mg/kg was administered to one of the treatment groups and 8 mg/kg to the other treatment group intraperitoneally. The effects of tocilizumab were revealed by examining pancreatic tissue of the rats histopathologically according to the Schonberg scoring system. Results: A comparison between tocilizumab treatment group and AP control group provides statistically significant improvement in AP (p Conclusion: Our study points out that tocilizumab may be an effective agent for pancreatitis treatment. Cite this article as: Hançerli Y, Kaplan M, Tanoğlu A et al. Efficacy of tocilizumab treatment in cerulein-induced experimental acute pancreatitis model in rats. Turk J Gastroenterol 2017; 28: 485-91.